A Content Analysis of Corporate Blogs to Identify Communications Strategies, Objectives and Dimensions of Credibility. Issue 4 (7th June 2019) - Colton, Deborah A.; Poploski, Sharon P.
Abstract: The purpose of this study is to examine corporate blogs to understand how they reflect communications objectives and strategies and represent dimensions of corporate credibility. Emergent themes and frameworks of corporate credibility provided the theoretical framework for this study. A content analysis of corporate blogs was conducted in a multi-stage process, two researchers coded 534 blog posts from 41 corporate blogs. The findings indicate a broad range of communication messages with the majority pertaining to the corporation itself followed by product-related strategies. Corporate blogs afford organizations the opportunity to interact directly with their audiences. Determining topics should be dependent upon the objectives that the organization has for the corporation and its blog. This study sheds light on the dimensions of corporate credibility that may be appropriate for organizations to consider in their online communications and promotion.